Application of remote learning in studying of plasma physics - Turekhanova, K.M.; Akimkhanova, Zh.E.; Nurzhanova, M.S. (Recent Contributions to Physics, 2017)
Plasma physics attract scientists from different countries day by day with its still unknown aspects. Therefore, the lack of complete information should not constrain the interest of our young generation in the presence of many news and forecasts in the world on this part. Our task in the teaching of plasma physics is to select an accessible teaching methodology that allows us to track all current changes in plasma physics in a timely and complete manner. In connection with this problem, the site is developed in present work for distance education by the course of plasma, which is accessible and convenient for using and understanding. It has parts of lectures, practical tasks, feedback comments, list of literatures and new articles about plasma. The objective and observing independent work is used on the basis of distance learning, which is trained with special educational and methodological materials. The components and methods of distance educations are directed to optimal and effective teaching. This article describes distance learning on the course of plasma physics, the content and relevance of training.